VUCA and Luxury - Challenges for Export Dependent Gem and Jewelry SMEs and What Can Be Learnt from the Past - Hjornered, Lars Jonas (Digital Repository of Theses - SSBM Geneva, 2025)
Gems and jewelry are among Thailand’s leading export products with approximately 80% of output being exported. It is also a vital industry in terms of job creation, accounting for hundreds of thousands of jobs nationwide with most businesses being classified as Small and Medium Sized Enterprises (SMEs). Small businesses are often more exposed to challenges than bigger companies in times of uncertainty, something researchers refer to as ‘liability of smallness’. This liability of smallness is often linked with lack of resources, increased difficulties in accessing capital, loans, and their ability to keep key employes etc., all which becomes even more difficult in Volatile, Uncertain, Complex and/or Ambiguous (VUCA) environments. The reality becomes even more complex since gemstones and finished jewelry are considered discretionary products, meaning they are among the first purchases a wide range of consumers cut back on in times of uncertainty. Geopolitics, ESG trends, technological advancements, economic or political turmoil, international trade regulations along with other VUCA elements tend to have an impact on the performance of businesses. This study, therefore, intends to form a deeper understanding of the complex interrelation between Thai gem and jewelry SMEs and their competitiveness in the global VUCA environment. How export dependent gem and jewelry SMEs interpret their experiences of VUCA environments, construct their direction thereafter, and what meanings they attribute to these experiences. The idea is to generate an analysis which identifies VUCA factors related to the gem and jewelry industry and to widen the understanding concerning ways SMEs interpret and respond to these challenges through various means such as decision making, management, strategy, marketing, pricing, products, operations, technological advances et cetera and to explore which VUCA type stands most challenging going forward.